The Influence of Employee Engagement and Job Satisfaction on Organizational Citizenship Behavior Among Civil Servants at UPT Puskesmas Batang Tarang, Sanggau Regency 10000 c - Isnitta Aulya Sudirman; Arninda Arninda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the influence of employee engagement and job satisfaction on organizational citizenship behavior (OCB) among State Civil Apparatus (ASN) at UPT Puskesmas Batang Tarang, Sanggau Regency. The background of this research is based on the importance of human resource development in improving the quality of public services, especially in the health sector. The approach used is an associative quantitative approach, with data collection through questionnaires to 35 respondents using a total sampling technique. Employee engagement is measured through three main dimensions: vigor, dedication, and absorption. Job satisfaction is measured through five aspects: work, supervision, coworkers, promotion, and salary. Meanwhile, OCB is measured using five dimensions: altruism, conscientiousness, sportsmanship, courtesy, and civic virtue. The results of validity and reliability tests show that all instruments in this study are valid and reliable. Data analysis is conducted using multiple linear regression. The results indicate that employee engagement and job satisfaction simultaneously show a value of 27.783 with a significance of 0.000 < 0.05, positively and significantly influencing OCB. The results of partial significance tests (t-test) reveal that the Employee Engagement variable (X1) has a calculated t value of 5.261 with a significance level of 0.000, which means statistically this variable has a significant partial effect on OCB. Similarly, the Job Satisfaction variable (X2) shows a calculated t value of 5.001 with a significance value of 0.000, thus it can be concluded that this variable also has a significant partial effect on OCB, with a coefficient of determination (R²) of 0.635. This means that 63.5% of the variation in OCB can be explained by these two independent variables. Partially, each variable also has a positive and significant effect on OCB, with significance values below 0.05. This research provides theoretical and practical implications in human resource management, especially in creating a work environment that supports the enhancement of ASN engagement and satisfaction to strengthen OCB behavior and the quality of health services.